2016
DOI: 10.2214/ajr.15.14997
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Features of Biphenotypic Primary Liver Carcinoma (Hepatocholangiocarcinoma) and the Potential to Mimic Hepatocellular Carcinoma: LI-RADS Analysis of CT and MRI Features in 61 Cases

Abstract: Most biphenotypic primary liver carcinomas have features of non-HCC malignancy and can be correctly categorized as such. Addition of ancillary features to major features may improve diagnostic accuracy over systems in which only major features are used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(78 citation statements)
references
References 17 publications
5
71
1
1
Order By: Relevance
“…Nevertheless, our study revealed that mosaic architecture presented more in the cirrhosis background. Potretzke et al [10] indicated mosaic architecture as an ancillary feature favoring malignancy and HCC specifically, and the concurring more commonly seen mosaic architecture and HCC-like enhancement pattern in cirrhosis background of our study coincided with the theory to a cer- tain extent. This may be explained by the abundant fibrous stroma and segregation histopathologically which may be partly related to the disturbed blood supply and the distortion of the hepatic parenchyma under cirrhotic background.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Nevertheless, our study revealed that mosaic architecture presented more in the cirrhosis background. Potretzke et al [10] indicated mosaic architecture as an ancillary feature favoring malignancy and HCC specifically, and the concurring more commonly seen mosaic architecture and HCC-like enhancement pattern in cirrhosis background of our study coincided with the theory to a cer- tain extent. This may be explained by the abundant fibrous stroma and segregation histopathologically which may be partly related to the disturbed blood supply and the distortion of the hepatic parenchyma under cirrhotic background.…”
Section: Discussionsupporting
confidence: 91%
“…All lesions were hyperintense on DWI, and the marked restricted diffusion can raise suspicion for cHCC-CC, which was supported by Potretzke et al [10]. However, DWI is hampered by the low specificity, and there are substantial overlaps in the range of ADCs among cHCC-CC in normal, fibrotic, and cirrhotic livers.…”
Section: Discussionmentioning
confidence: 63%
“…The variable imaging appearance of cHCC-CC overlaps with that of both HCC and iCC, leading to frequent misdiagnosis as monophenotypic HCC or iCC [9][10][11]. While surgical resection likely confers the greatest survival benefit for eligible early stage cHCC-CC patients, post-surgical recurrence is common and most patients present with advanced disease not amenable to resection [1,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocholangiocarcinomas are rare primary "biphenotypic" hepatic malignancies that may show features overlapping HCC and ICC (109). Some authors suggest that the imaging features more closely resemble those of ICC and that prospective differentiation of ICC from a combined tumor can be difficult (109-111).…”
Section: Review: Li-rads Major Features For Hepatocellular Carcinoma mentioning
confidence: 99%